Phenotypic Evolution of Therapeutic Salmonella enterica Serovar Typhimurium after Invasion of TRAMP Mouse Prostate Tumor - Elizabeth Choe (American Society for Microbiology, 2014)
ABSTRACT Salmonella has been of interest in cancer research due to its intrinsic ability to selectively target and colonize within tumors, leading to tumor cell death. Current research indicates promising use of Salmonella in regular administrations to remove tumors in mouse models while minimizing toxic side effects. However, selection of mutants during such long-term tumor colonization is a safety concern, and understanding selection of certain phenotypes within a tumor is an important consideration in predicting the long-term success of bacterium-based cancer treatment strategies. Thus, we have made an initial examination of selected phenotypes in a therapeutic Salmonella enterica serovar Typhimurium population developed from an archival wild-type LT2 strain and intraperitoneally injected into a 6-month-old TRAMP (transgenic adenocarcinoma of mouse prostate) mouse. We compared the original injected strain to isolates recovered from prostate tumors and those recovered from the spleen and liver of non-tumor-bearing TRAMP mice through phenotypic assessments of bacteriophage susceptibility, motility, growth rates, morphology, and metabolic activity. Tumor isolate traits, particularly the loss of wild-type motility and flagella, reflect the selective pressure of the tumor, while the maintenance of bacteriophage resistance indicates no active selection to remove this robust trait. We posit that the Salmonella population adopts certain strategies to minimize energy consumption and maximize survival and proliferation once within the tumor. We find these insights to be nonnegligible considerations in the development of cancer therapies involving bacteria and suggest further examinations into the evolution of therapeutic strains during passage through tumors. IMPORTANCE Salmonella is of interest in cancer research due to its intrinsic abilities to selectively target, colonize, and replicate within tumors, leading to tumor cell death. However, mutation of strains during long-term colonization within tumors is a safety concern, and understanding their evolution within a tumor is an important consideration in predicting the long-term success of bacterium-based cancer treatment strategies. Thus, we have made an initial examination of phenotypically diverse Salmonella colonies recovered from a therapeutic Salmonella strain that we developed and injected into prostate tumor-bearing mice. We compared the bacteriophage susceptibility, motility, growth rates, morphology, and metabolic activity of the original therapeutic strain to those of strains recovered from prostate tumors of tumor-bearing mice and the liver and spleen of non-tumor-bearing mice. Our results suggest that the Salmonella population adopts certain strategies to minimize energy consumption and maximize survival and proliferation once within the tumor, leading to phenotypic changes in the strain.